Rearrange formula

• Nov 19th 2009, 06:40 PM
nexer
Rearrange formula
i need to make c the subject in this formula? any help would be nice please.

s=c+mt
• Nov 19th 2009, 06:44 PM
ukorov
Quote:

Originally Posted by nexer
i need to make c the subject in this formula? any help would be nice please.

s=c+mt

c = s - mt
• Nov 19th 2009, 06:59 PM
Wilmer
Quote:

Originally Posted by nexer
i need to make c the subject in this formula? any help would be nice please.
s=c+mt

Nexer, any reason why you couldn't solve that?
• Nov 19th 2009, 08:47 PM
ukorov
Quote:

Originally Posted by Wilmer
Nexer, any reason why you couldn't solve that?

because he has just started learning algebra
• Nov 19th 2009, 10:46 PM
nexer
feel like i really suck at algebra, like i also need to know to rearrange the formula so i can make t the subject

S=c+mt

i got s-c/m=t

? Guessing wrong?
• Nov 20th 2009, 03:16 AM
HallsofIvy
Quote:

Originally Posted by nexer
feel like i really suck at algebra, like i also need to know to rearrange the formula so i can make t the subject

S=c+mt

i got s-c/m=t

? Guessing wrong?

The problem is "guessing" at all! The only reason c, in s= c+ mt is not "by itself" already is that mt is added to it. To "undo" that, do the opposite: the opposite of "add mt" is "subtract mt". Subtract mt from both sides to get s-mt= c which is the same as c= s- mt.

Now, t, in s= c+ mt is not "by itself" is that two things have been done to it: to get to "c+ mt" from t, you would "multiply by m" and "add c" in that order. To "undo" it, do the opposite things in the opposite order: first "subtract c" then "divide by t".

From s= c+ mt, subtracting c from both sides gives s- c= mt. Now divide both sides by m- but be sure to show that the entire right side, s- c, is divided by m, not just "c": use parentheses (s-c)/m= t, not "s- c/m" which means s- (c/m)!
• Nov 20th 2009, 06:03 AM
nexer
Sorry, it wasn't actually a "guess" i tried to work it out, that final answer is what i had on paper!
• Nov 20th 2009, 06:16 AM
Wilmer